The Effect of CEO Gender on Dividend Policy: A Multi-Theoretical Approach - Moh. Baqir Ainun; Nur Qoudri Wijaya; Ahmad Ghufrony; Liyanto Liyanto; Stevan Ariputra Harmanto; Diah Anggraeni Pitaloka (UNIVED Press, 2026)
This study examines the effect of CEO gender on dividend policy in Indonesia, motivated by the underrepresentation of female CEOs (around 4% of large firms) and the inconsistent findings of prior studies. Using a multi-theoretical framework—Upper Echelons, Risk Aversion, Agency, Gender Role, and Signalling theories—the study provides a comprehensive lens to explain dividend decisions. Secondary data from manufacturing firms listed on the Indonesia Stock Exchange for 2019–2023 were analyzed using multiple linear regression, controlling for profitability, liquidity, leverage, growth, and firm size. The findings show that female CEOs are more likely to distribute dividends, reflecting leadership traits, cautious and risk-averse behavior, agency conflict reduction, socially driven gender roles, and signaling motives. This study contributes to the literature by integrating diverse theories and emphasizes the strategic importance of gender diversity in top management for improving transparency and investor confidence in emerging markets.